Proceeding - Factors Affecting Household Industries In Increasing Revenues - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Proceeding - Factors Affecting Household Industries In Increasing Revenues